Hereditary diffuse gastric cancer: association with lobular breast cancer - Kasmintan A. Schrader; Serena Masciari; Niki Boyd; Sara J. Wiyrick; Pardeep Kaurah; Janine Senz; Wylie Burke; Henry T. Lynch; Judy E. Garber; David G. Huntsman (2007)
Hereditary diffuse gastric cancer (HDGC) has been shown to be caused by germline mutations in the gene CDH1 located at 16q22.1, which encodes the cell-cell adhesion molecule, E-cadherin. Not only does loss of expression of E-cadherin account for the morphologic differences between intestinal and diffuse gastric cancer (DGC) variants, but it also appears to lead to distinct cellular features which appear to be common amongst related cancers that have been seen in the syndrome. As in most hereditary cancer syndromes, multiple organ sites may be commonly affected by cancer, in HDGC, lobular carcinoma of the breast (LBC) and possibly other organ sites have been shown to be associated with the familial cancer syndrome. Given the complexity of HDGC, not only with regard to the management of the DGC risk, but also with regard to the risk for other related cancers, such as LBC, a multi-disciplinary approach is needed for the management of individuals with known CDH1 mutations.